The Use of Word-Processing to Decrease the Students’ Errors in Writing Descriptive Text in SMAN 1 BABAT LAMONGAN (RETAIN, 2014)
The Use of Word-Processing to Decrease the Students’ Errors in Writing Descriptive Text in SMAN 1 BABAT LAMONGAN Farid Fakhrudin English Education, Faculty of Languages and Arts, State University of Surabaya fafa_fakhrudin@yahoo.co.id Ahmad Munir, S.Pd., M.Ed, Ph.D English Education, Faculty of Languages and Arts, State University of Surabaya Abstract The objective of this research is to find out whether there is significant difference in the number of error between handwritten essay and those are written by using word-processing and the students’ view on the advantage of word-processing in their writing. The research is quasi-experimental research and the subject of this research was the tenth grade students of SMA Negeri 1 BabatLamongan. This research consisted of one class of X-6 (37 students). The researcher did the observation and also usedtest and questionnaire as the research instruments. It was found that word-processing was helping the student to decrease their errors. There are 164 errors in the pretest and 168 errors in the posttest, but there is only 60 errors happened when they used word-processing. The students also gave a positive respond in the using of word-processing in the writing class. They felt comfort when they write by using word-processing, they did not nervous and they can more focus when they work with it. The result of this research showed that there is significant difference in the number of grammatical errors in their handwritten essays and those written by using word-processing. In conclusion, the use of word-processing in learning to write can decrease students’ chances to commit errors in their writing. Thus, teachers can apply this in their classes. Abstrak Tujuandaripenelitianiniadalahmenemukanbahwaadaperbedaandalamjumlahkesalahanantara essay yang ditulissecara manual dan essay yang ditulismenggunakan word-processing sertamelihatresponmurid-muriddarikeuntunganmenggunakan word-processing saatmenulis essay.Jenispenelitian in adalah quasi-experimental dansubjekdaripenelitianiniadalahmurid-muridkelas X di SMAN 1 BABAT LAMONGAN.Penelitianiniterdiridari 37 murid di kelas X-6.Penelitimelakukanobservasidanjugamenggunakan test dankuestionairsebagai instrument penelitian. Di dalampenelitianditemukanbahwa word-processing membantumurid-muridmengurangikesalahanmereka. Ada 164 kesalahan di pretest dan 168 kesalahan di posttest, tetapihanyaterjadi60 kesalahanketikamerekamenggunakan word-processing. Murid-muridjugamemberikanresponpositifdalampenggunaan word-processing di dalamkelasmenulis.Merekamerasanyamanketikamerekamenulismenggunakan word-processing, merekatidakmerasagrogidanmerekalebihfokusketikamenulismenggunakan word-processing. Hasildaripenelitianinimenunjukkanbahwaadaperbedaandalamjumlahkesalahanantara essay yang ditulissecara manual dan essay yang ditulismenggunakan word-processing. Kesimpulannya, penggunaan word-processing dalampembelajaranmenulisdapatmengurangikesempatanmuriduntukmelakukankesalahan di essay mereka.Olehkarenaitu, guru dapatmenggunakan word-processing dalamkelasmereka. INTRODUCTION EFL learners face many difficulties in learning language skills such as listening, speaking, reading, and writing (AbuSeileek, 2004). Abu Seileek was conducting a survey to know the most difficult EFL skill to learn. He asked 85 freshmen in the Senior high school in King Saudi about the most difficult EFL skill to learn. More than 67% of them said that it was writing, and most of them (70%) attributed this to using unsuitable methods and techniques for teaching the skill of writing. Writing is a complex skill for the students who want to learn English. It needs long processes and takes more time during the processes. Hulstjin (2000) state that students are often making many mistakes in a structure arrangement, grammar, and sometimes they put wrong article for countable and uncountable noun. As stated by Bram (1995) that writing is one the ways to communicate beside the spoken language. It can be a tool to delivered information, share about everything and ask the reader to communicate as using spoken language. Nunan(2003) pointed out that writing is a mental work of inventing ideas, thinking about how to express and organize them into statements and paragraphs that will be clear to the readers. The grammatical errors made by the students occur mostly because of the students’ lack of competence in internalizing the structure of the foreign language. Brown (2007, p. 226) states that mistake is a performance error that is either a random guess or “slip” in that is a failure to utilize a known system correctly. Sometimes it happened when the students made a sentence, they translate an Indonesia sentence directly into English without knowing that grammar in English are very different to Indonesia, and it cannot be translated directly without knowing the grammatical rules. For example, his hair is long and his skin white, instead of his skin is white. I took this example from the students’ pretest; he wanted to write ”rambutnyapanjangdankulitnyaberwarnaputih” in English, he translated directly from Indonesian language without knowing the grammatical rules. Another example was also taken from the students’ pretest, my father born 19 January 1969, instead of the correct sentence is my father was born on 19 January 1969. As Brown has said that errors cannot be self-corrected, that means, it needs other people to correct it. Teacher cannot always ignore students’ correctness in using English. Correction is used positively to support students’ learning (Edge, 1989). For those reasons, students need to be more careful in producing or writing a composition. It needs more control to make a good writing. The difficulty in producing a good composition related to the criteria must be accounted in writing. Brown (2004, p. 246)states that those criteria that include the content (30 points), organization (20 points), vocabulary (20 points), grammar (25 points) and mechanism (5 points). While grammar takes 25 points of the overall criteria, means that students should give more attention in a grammar when they produce the text. In this case, the researcher will focus on one text type, which is descriptive text. Descriptive text is a text that is aimed to describe a particular person, place, or thing (Depdiknas, 2003, p. 49).It tells the reader about the detail and factual information of the objects described. In fact, the students still make mistakes when they produce descriptive text. It happened continuously when they produce the text, so, here the researcher wants to help the students to decrease their grammar mistakes when they produce a text like descriptive text. This research attempted to apply word-processing technique to decrease student’s errors in writing process. Word processing is the most common computer application, or in general, the people knew that the word-processing is a Microsoft word. It can be used for doing homework, writing reports, letters, brochures, and much more. After you learn the basics, let your imagination soar to construct creative documents. Many studies reported that CALL is useful for EFL learners, and learners generally have a positive attitude towards using technology for learning language skills like writing because technology has a positive impact on the learning or teaching process (Neu, 1991); (Phinney M. , 1991); (Nash & Chen, 1989); (Phinney M. a., 1988); (Herrmann, 1987); (Daiute, 1984). Stevens (1999) Recommended using the computer for learning the skill of writing. He believed that the word processor had a positive effect on the development of students’ achievement in writing. Cochran-Smith (1991)also reports that student makes more revisions when writing with a word-processing. The students made more revisions because the word-processing can facilitated the student to give a direct feedback when they made an error in their writing. Cobine(1997) found that the computer has a good effect on the improvement of the skill of writing. Learners could conceivably experiment with phrase and sentence structure, and practice rhetorical grammar through using computer linguistic functions. Greenfield (2003) reported that students enjoyed the CALL class and made significant progress in writing. Based on those previous studies above, word processing gives a positive effect and can improve the students writing ability. Yet, the improvement is not specific to errors reduction. Therefore, this research has been set to find out whether there is significant difference in the number of grammatical errors in their hand written essays and those are written by using word-processing. The students’ view on the advantage of using word-processing in reducing writing errors were also sought. METHOD This study is a quasi-experimental study because the researcher conducted the research in the classroom without changing their grouping (in tach group) rather than in the laboratory. The researcher used one class to conduct the research, this design is called one group-time series (Cohen, Manion, & Morrison, 2007, p. 284). There is no control group and experimental group, because this only one group was given a pretest and posttest. The time series used repeated test both before and after the treatment, which, in effect, enables the participants to become their own control (Cohen, Manion, & Morrison, 2007). This subject of this research was X-6 in SMAN 1 BABAT LAMONGAN. These students were chosen because the students are the fresh graduate and they had a little understanding in English grammar. They had an obstacle and made more mistakes in writing. Therefore, here the researcher wanted to help them to decrease their grammar by using the media word-processing and the researcher wanted to know their responses when they used that media in writing class. The researcher hopes that it can help them in decreasing their errors and they give a positive respect. This research used test, questionnaire, and observation. Test was used to find out the number of grammatical errors in both pretest and posttest, while questionnaire was used to see the students’ view when they used word-processing in writing class and observation was used to see the students action when they worked by using word-processing. After collecting the data, both number of grammatical error and the students statement from the questionnaire. The researcher identified the errors on grammatical construction in the students’ descriptive writing. He collected all the error sentences from each subject and put them into checklist. The sentence was considered as an error sentence if there was any deviation in applying the rules of grammatical construction. The researcher underlined the area of errors in each error sentence because it is possible that there were more than one error in one sentence. After being identified, all errors found were categorized into the types of errors. In order to make the classification easier, the researcher compared the sentences contained error with the correct form. The classification was based on surface strategy taxonomy proposed by Dulay(1982). This taxonomy was chosen because it showed the cognitive process that underlined the learners’ reconstructions of the new language learned. There are four types of errors according to this taxonomy; they are omission, addition, misformation, and misordering. The next step in analyzing the data after identifying and classifying the errors was counting the frequency of occurrences of errors on each type of errors. The calculation of the number of errors did not do per wrong sentences but per one type of error. It was done because it was possible that there were more than one error in a sentence. In this study, the researcher presented the frequency of occurrences of errors in the form of percentage in order to make it clearer to the reader. The description of the properties of the variable included means, standard deviation, and t test would be made to find out if there is significant difference in the number of grammatical error in pretest, posttest, and word-processing by using SPSS. After that, the researcher would answer the second research question. The researcher used the second data to answer the second research. The researcher used the second data that was the students’ statement from the questionnaire. The researcher collected the questionnaire and analyzed it and this data would be served at percentage form. The result of this data would show the students’ view when they were given the media. RESULTS AND DISCUSSION Based on the students’ essays, there were 37 descriptive text analyzed. There were 164 errors found in the hand written in pre-test (113 errors in mission, 21 errors in addition, 24 errors in misformation, and 6 errors in misordering), 60 errors were found in the written by using word processing (16 errors in omission, 12 errors in addition, 21 errors in misformation, and 11 errors in misordering) and 168 errors in the hand written in posttest (96 errors in omission, 32 errors in addition, 35 errors in misformation, and 5 errors in misordering). After the data was counting by using SPSS, the researcher found that the mean of total error in pretest is 4.4054; the mean of total errorsin computer is 1.6216, and the mean of total errors in posttest is 4.5405.Those results indicate that the students made more errors in pretest and in the posttest than in computer. The t-value between total errors in pretest and total errors in computer is 10.557 and the significant 2-tailed is .000. and the t-value between total errors in computer and total errors in posttest is -1.89614, the minus number showed that after using computer in writing class and the students took a posttest, the number of errors are increasing. The significant 2–tailed is .000, that result showed that there is significant difference in the number of errors between those variables. The students showed positive response in using word processing in the class writing. Based on Greenfield (2003), the researcher found that the students feel comfort and enjoy when they write by computer. From one of the statement above more than 82% students said that work with word-processing in the class writing is interesting. They did not feel nervous when they produced the text. They felt enjoy when write by using word-processing and 81% students said they got more ideas when they produced the text. They also liked to write by using word processing because it can give them directly feedback when they made mistake in grammatically. so, they can change their produce easily than using traditional style. They should not wait for teachers’ feedback and for about 60% students said that they do not need teachers’ feedback when they used word-processing. The researcher found that the students made total 164 errors in pretest and 168 errors in postest. As stated by Hulstjin(2000), students are often making many mistakes in a structure arrangement, grammatically, and sometimes they put wrong article for countable and uncountable noun. As state by Lengo(1995) errors are believed to be an indicator of the learners’ stages in their target language development. When they worked with word-processing, they were so quite. That fact is similar to Greenfield’s (2003) observation that students enjoyed the CALL class and made significant progress in writing. That was so different when they work in class or in handwritten; they were so crowded and going anywhere, they cannot focused on their work. The researcher found 60 errors when they worked by using word-processing. When the student worked by using word-processing, they made more revisions, as stated by Cohran-Smith (1991) that the students make more revisions when writing with a word-processing. It happened because word-processing could give the students feedback directly and it proved that it could decrease the students’ errors significantly. Steven (1999) point out that he believed that the word-processing had a positive effect on the development of the students’ achievement. He also believed that word processing can improve the learners’ ability in writing skill and it can help the learners to overcome their problem in grammatical error. Here, the word-processing proved that it could decrease the students’ error. The total errors were decrease significantly, if in the pretest the students’ made 164 errors and in the posttest they made 168 errors As stated by Cobine(1997) that computer tutorials offered them grammatical choices and then provided immediate feedback on structures. So, the answer for the first question “is there a significant difference in the number of grammatical errors in their handwritten and that written by using word-processing?” is yes, it is. There is a significant difference in the number of grammatical errors in their handwritten and that written by using word-processing. From the data of the questionnaire that was collected in the last meeting by the researcher showed that the students felt enjoy when they worked by word-processing. They feel that deal with computer in the class writing is something interest. Most of them, they ever worked with computer, but, in their English class, they never worked with word-processing. So, when the students deal with the word-processing in their English class, which was something new for them. This view held by my student in my study is similar to Cunningham’s (2000) study. In his study, he found that the computer-based writing class to be challenging and comfortable. After they deal worked with word-processing, they prefer used word-processing in their writing class, because the word-processing can give them a feedback directly, it was so helpful for them. CONCLUSION There are two conclusions for tis research. First, the result of this study showed that by using word-processing the students made improvement in their writing. The improvement is seen from the reduction of the number of errors. This make the alternative hypothesis that said that there is significant difference in the number of grammatical errors in their handwritten essays and those written by using word-processing is acceptable. The second conclusion is that the students get benefits from the use of word-processing in their writing class. It is concluded that the students’ were good, in terms they felt enjoy when they deal with word-processing. They also said that used word-processing in the class writing was interesting. All of them gave a positive respect on the advantage of word-processing. REFERENCES BIBLIOGRAPHY BIBLIOGRAPHY AbuSeileek, A. (2004). Designing a CALL Program for Teaching Writing to Jordanian EFL Learners and Its Effect. Amman: Amman Arab University. Bram. (1995). Problem solving strategies for writing. New york: Longman. Brown, H. D. (2004). Language Assessment. In Principles and Classroom Practice. San Francisco: Longman. Brown, H. D. (2007). Principle of Language Learning and Teaching, Fifth Edition. New York: A Pearson Education Company. Cobine, G. (1997). studying with the computer. Retrieved december wednesday, 2012, from ERIC Digest: http://www.askeric.org Cochran-Smith, M. (1991). Learning to write differently. Norwood, NJ: Ablex. Cunningham, K. (2000). Integrating CALL into the Writing Curriculum. The Internet TESL Journal, 6, No. 5. Daiute, C. (1984). Can the Computer Stimulate Writer’s Inner Dialogues? Urbana: NTCE. Depdiknas. (2003). Standar Kompetensi Mata Pelajaran Bahasa Inggris untuk SMA dan MA. Jakarta: Depdiknas. Dulay, H. (1982). Language Two. New York: Oxford University Press. Edge, J. (1989). Mistakes and Correction. London: Addison Wesley Longman. Greenfield, R. (2003). Collaborative E-mail Exchange for Teaching Secondary ESL. Language Learning and Technology, 7, no. 1(A Case in Hong Kong), 46-70. Herrmann, A. (1987). An Ethnographic Study of a High School Writing Class Using Computers: Marginal,Technically Proficient, and Productive Learners. New York: Random House. Hulstijn, J. (2000). The Use of Computer Technology in Experimental Studies of Second Language Acquisition. Language Learning and Technology, 3, No. 2(A Survey of Some Technique and Ongoing Studies ), 32-43. Lengo, N. (1995). What is an Error? Vol.33, No.3. Nash, T. H., & Chen, S. (1989). An Evaluation of Computer-aided Composition. Taipei, Taiwan: The Crane. Neu, J. a. (1991). Computer-assisted Language Learning and Testing: Research Issues and Practices. New York: Newbury House. Nunan, D. (2003). Practical English Language Teaching. Singapore: The Mc. Graw Hill Companies. Phinney, M. (1991). Computer-assisted Writing and Writing Apprehension in ESL Students. . New York: Newbury House. Phinney, M. a. (1988). ESL Student Responses to Writing with Computers. . New York: Newbury House. Stevens, V. (1999). Language Learning Techniques Implemented through Word Processing. Retrieved december wednesday, 2012, from http://www.netword.com/esl_home